Peningkatan Hasil Pembelajaran Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Two Stay Two Stray di Kelas IV MI no.41/e3 Semerap - Al an Sori, Muhammad Redho; Muhammadi, Muhammadi; Amini, Risda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study was to describe and increase in student learning outcomes in social studies learning by using the Make a Match model in the fourthh grade of elementary school. Types of this research was classroom action research with qualitative and quantitative approach. The research subject was 24 grade IV students. The research procedure consistend of planning, implementing, observing, and reflecting. The result of the study showed and increase in aspects: a) RPP cycle I with an average of 82% and cycle II 90,90%, b) implementation on the aspect of the teacher cycle I with an average of 78% and the second cycle 92,5%, the aspect of the students of the first cycle with an average 70% and cycle II 87%, c) learning outcomes in the first cycle with an average of 70,49% and cycle II 87%. The conclusions from the result of the research conducted are using the Make a Match model can improve student learning outcomes in social stundent learning in class IV MI no.42/e3 Semerap Kabupaten Kerinci.